Removable Partial Denture Treatment in A-32 Years Old Patient: Case Report - Aldita Indria; Agung Priyambodo; Dharma Aprianto (Health & Medical Sciences, 2026)
This case report presents the prosthodontic management of a 32-year-old female patient who attended YARSI Dental Hospital, Jakarta, with complaints of discomfort and impaired chewing due to missing posterior mandibular teeth. Teeth 36, 46, and 47 had been extracted two years earlier as a result of extensive caries. The patient reported no systemic diseases, allergies, or parafunctional habits and demonstrated satisfactory oral hygiene. Clinical and radiographic examinations revealed favorable oral conditions, including healthy oral mucosa, adequate vestibular depth, and symmetrical facial features. Based on these findings, the patient was diagnosed with Kennedy Class III modification 1 partial edentulism. After receiving a detailed explanation of the treatment plan and providing informed consent, rehabilitation using a tooth- and mucosa-supported acrylic removable partial denture was selected to restore masticatory function and comfort. Anatomical impressions were taken using irreversible hydrocolloid to obtain study models. The denture was designed with appropriate clasp assemblies, rest seats, and an acrylic base extending to the retromolar pad. Surveying, blockout procedures, rest seat preparation, jaw relation recording, tooth arrangement, and wax try-in were performed sequentially before laboratory processing with heat-cured acrylic resin. Upon insertion, the denture exhibited satisfactory retention, stability, occlusion, and patient comfort without causing soft tissue irritation. Post-insertion instructions were provided, and follow-up visits were conducted to evaluate adaptation and function. Minor occlusal adjustments were required during the initial follow-up. Subsequent evaluations demonstrated improved masticatory comfort, good adaptation, and high patient satisfaction. This case highlights the effectiveness of systematic clinical and laboratory procedures in achieving successful outcomes with acrylic removable partial dentures.